IMPROVING STUDENTS’ PRONUNCIATION BY USING TONGUE TWISTERS TECHNIQUE - Umaraliyeva , Munojatxon Mashrabovna; Mukhammadjonova , Madinabonu Isroiljon qizi (Educational Research in Universal Sciences, 2023)
This article aims to investigate how tongue twisters can enhance students’ pronunciation skill and its importance in impacting positively to loose learners hesitation. Since, most language learners have challenges to speak clearly and to use correct intonation. So this study offer a feasible solution by using tongue twisters in order to improve the ability to use word stress, the ability in using correct intonation and to decrease their pauses in language acquisition.